2022
DOI: 10.1021/acsami.2c17557
|View full text |Cite
|
Sign up to set email alerts
|

Printed Antifouling Electrodes for Biosensing Applications

Abstract: Biosensors based on miniaturized, functional electrodes are of high potential for various biosensing applications, especially at the point-of-care setting among others. However, the sensor performance of such electrochemical devices is still strongly limited, especially due to surface fouling in complex sample fluids, such as blood serum. Electrode coatings based on conductive nanomaterials embedded in antifouling matrices offer a promising strategy to overcome this limitation. However, known composite coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This observation can be explained by the long chain length and insulating nature of PEG. Furthermore, it is consistent with previous findings, suggesting that PEG hinders the electron transfer between the porous surface of the LSGE and the redox species . In contrast, the integration of the ZW moieties on the LSGE does not appear to affect the current response.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation can be explained by the long chain length and insulating nature of PEG. Furthermore, it is consistent with previous findings, suggesting that PEG hinders the electron transfer between the porous surface of the LSGE and the redox species . In contrast, the integration of the ZW moieties on the LSGE does not appear to affect the current response.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is consistent with previous findings, suggesting that PEG hinders the electron transfer between the porous surface of the LSGE and the redox species. 37 In contrast, the integration of the ZW moieties on the LSGE does not appear to affect the current response. This is reflected in the limited 3.5% reduction of the current response of LSGE/ ZW (Figure 3e).…”
Section: Production Of Lsgesmentioning
confidence: 98%
See 2 more Smart Citations
“…The 2.5/1 ratio of polymer/CNTs was identified as the most effective combination due to its highest electroactive surface area (EASA) and highest anti-fouling properties against BSA, with only a very small decrease in EASA observed after 1 h (Figure 3B). [81] The prepared electrodes enabled the successful electrochemical detection of the inflammatory biomarker C-reactive protein (CRP) using chronoamperometry in undiluted human blood serum, using a CRP capture antibody (Ab) as the ligand. Similarly, Chocholova et al reported the fabrication of thin film poly{4-[(3-methylacrylamidopropyl)dimethylaminobromobutyrate]-co-[N-methacryloyl-4-azidoaniline]} and poly{4-[(3-methylacrylamidopropyl)dimethylamino-bromoacetate]-co-[N-methacryloyl-4-azido-aniline]} (CBAmN 3 copolymer)-based hydrogels on carbon SPEs that were further functionalized with human epidermal growth factor receptor 2 (HER2) antibodies, facilitating the accurate detection of the breast cancer biomarker HER2 protein [82] Relative to photopolymerization, grafting via gamma ray initiation offers several advantages including the elimination of the need for catalysts or initiators and the ability to graft with proteins and other biomolecules at low temperatures.…”
Section: Photopolymerizationmentioning
confidence: 99%